2018
DOI: 10.1111/adj.12609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chelating agent and acids on Biodentine

Abstract: Changes in the topography, microhardness and POBS of Biodentine are associated with irrigant agent used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(44 reference statements)
1
4
0
1
Order By: Relevance
“…As for BCP, Sharma concluded that EDTA reduced microhardness (with the potential of losing its structural integrity with prolonged EDTA exposure), while NaOCl increased microhardness. These findings are in accordance with other studies . There are no evidence‐based recommendations regarding the ideal time to leave BCP to set before subjecting the material to irrigants during root canal therapy.…”
Section: Introductionsupporting
confidence: 88%
“…As for BCP, Sharma concluded that EDTA reduced microhardness (with the potential of losing its structural integrity with prolonged EDTA exposure), while NaOCl increased microhardness. These findings are in accordance with other studies . There are no evidence‐based recommendations regarding the ideal time to leave BCP to set before subjecting the material to irrigants during root canal therapy.…”
Section: Introductionsupporting
confidence: 88%
“…Furcal perforation should be repaired as soon as possible, before proceeding with the root canal treatment to favor the outcome of the endodontic treatment. [13] An ideal perforation repair material should remain in place under dislodging forces, such as mechanical loads of occlusion or the condensation of restorative materials over it and provide a tight seal between the oral environment and periradicular tissues. [9] The present study evaluated the effect of irrigating solutions namely sodium hypochlorite and EDTA on the microhardness of MTAA, Biodentine and Pozzolan cement(Endocem MTA) after 24hrs and 8 days.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that maleic acid, EDTA and phosphoric acid reduced the microhardness of Biodentine. [13] Guneser et al have evaluated the influence of different root canal irrigating solutions on the push out bond strength of BD and MTA. They concluded that BD demonstrated a considerable performance after being exposed to root canal irrigants as compared to MTA.…”
mentioning
confidence: 99%
“…При такой толщине Биодентин обладает отличной способностью противостоять смещению [93,97] и перелому корня [92] по сравнению с Биоагрегатом и MTA, тогда как чрезмерная толщина материала может оказывать неблагоприятное воздействие на перелом и сопротивление нагрузкам [30]. На прочность связи Биодентина с дентином корня зуба, как и у других представителей биокерамики на основе силиката кальция, могут влиять вещества, используемые при эндодонтическом лечении зубов, такие как ирриганты, хелатирующие агенты и кислоты [13]. Так, прочность связи Биодентина и его герметизирующая способность были усилены, когда ирригация корневого канала проводилась с использованием гипохлорита натрия и физиологического раствора или смеси NaOCl и 1-гидроксиэтан-1,1-дифосфоновой кислоты (HEDP) [65], в то время как использование ЭДТА значительно увеличило микропротекание Биодентина [9].…”
Section: биокерамикаunclassified